Movement therapy in advanced heart failure assisted by a lightweight wearable robot: a feasibility pilot study - Isabell Anna Just; Denis Fries; Sina Loewe; Volkmar Falk; Nikola Cesarovic; Frank Edelmann; Anna Feuerstein; Florian L. Haufe; Michele Xiloyannis; Robert Riener; Felix Schoenrath (ESC Heart Failure)
Abstract Aims The aim of this pilot study was to investigate the safety, feasibility, tolerability, and acceptability of an assisted mobilization of advanced heart failure patients, using a lightweight, exoskeleton‐type robot (Myosuit, MyoSwiss AG, Zurich, Switzerland). Methods and results Twenty patients in functional NYHA class III performed activities of daily life (ADL, n = 10) or participated in a single, standardized, 60 min rehabilitation exercise unit (REU, n = 10) with and without the Myosuit. The outcome assessment included the evaluation of vital signs, adverse events, rates of perceived exertion and dyspnoea (RPE, RPD), the ability to perform ADL or REU, and the individual acceptability. The mean age of the subjects was 49.4 (±11.0) years; 80% were male. The mean left ventricular ejection fraction was 22.1% (±7.4%) and the median NT‐proBNP 2054 pg/mL (IQR 677, 3270 pg/mL). In all patients, mobilization with the Myosuit was feasible independently or with minor support. The mean individual difference in the total walking distance of the patients without and with robotic assistance was −26.5 m (95% confidence interval (CI) −142 to 78 m, P = 0.241). No adverse events occurred. RPE and RPD showed no significant difference with or without the device (ADL: RPE −0.1 m, 95% CI −1.42 to 1.62, P = 0.932 and RPD −0.95 m, 95% CI −0.38 to 2.28, P = 0.141; REU: RPE 1.1 m, 95% CI −2.90 to 0.70, P = 0.201 and RPD 0.5 m, 95% CI −2.02 to 1.02, P = 0.435). All median responses in the acceptability questionnaire were positive. The patients felt safe and enjoyed the experience; 85% would be interested in participating in robot‐assisted training on a regular basis. Conclusion This feasibility pilot trial provides first indications that a robotic exoskeleton‐assisted mobilization of patients with advanced heart failure is safe, feasible, well‐tolerated, and well‐accepted. The results are highly encouraging to further pursue this innovative approach in rehabilitation programmes. This trial was registered at ClinicalTrials.gov: NCT04839133.